Live Streaming and Short Video Marketing in E-Commerce: an AISAS Model Analysis - Ananda Desmayonda; Alim Setiawan Slamet; Jono M. Munandar; Furqon Syarief Hidayatulloh (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In recent years, the development of digital technology has driven significant changes in Indonesian consumption patterns, as reflected in the widespread use of e-commerce as a primary shopping platform. This study aims to examine the influence of live streaming and short video marketing on consumer behavior stages based on the AISAS (Attention, Interest, Search, Action, Share) model. The study involved 312 respondents who were active users of e-commerce platform XYZ in the Greater Jakarta area, selected through a purposive sampling technique. The research instrument was an online questionnaire that met the validity and reliability criteria. Data were analyzed using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) with SmartPLS version 4.0 software. The results show that both live streaming and short video marketing have a positive and significant influence on all stages of the AISAS model. These findings indicate that interactive, visually oriented marketing strategies can effectively enhance attention, stimulate interest, encourage information searches, and drive purchase and sharing decisions on e-commerce platforms.